Can internet search queries be used for dengue fever surveillance in China?. (October 2017) - Guo, Pi; Wang, Li; Zhang, Yanhong; Luo, Ganfeng; Zhang, Yanting; Deng, Changyu; Zhang, Qin; Zhang, Qingying
Highlights: Traditional surveillance system of dengue gives the reports with time lags. Baidu search queries were effectively used to monitor in a timely fashion dengue in China. The findings will help to improve traditional surveillance systems for dengue. Abstract: China experienced an unprecedented outbreak of dengue fever in 2014, and the number of cases reached the highest level over the past 25 years. Traditional sentinel surveillance systems of dengue fever in China have an obvious drawback that the average delay from receipt to dissemination of dengue case data is roughly 1–2 weeks. In order to exploit internet search queries to timely monitor dengue fever, we analyzed data of dengue incidence and Baidu search query from 31 provinces in mainland China during the period of January 2011 to December 2014. We found that there was a strong correlation between changes in people's online health-seeking behavior and dengue fever incidence. Our study represents the first attempt demonstrating a strong temporal and spatial correlation between internet search trends and dengue epidemics nationwide in China. The findings will help the government to strengthen the capacity of traditional surveillance systems for dengue fever.